Contracting with Repeated Moral Hazard and Private Evaluations - Fuchs, William (American Economic Review, 2007)
A repeated moral hazard setting in which the Principal privately observes the Agent's output is studied. The optimal contract for a finite horizon is characterized, and shown to require burning of resources. These are only burnt after the worst possible realization sequence and the amount is independent of both the length of the horizon and the discount factor. For the infinite horizon. it is shown that there is no loss from restricting the analysis to contracts in which the Agent receives a constant efficiency wage and no feedback until he is fired. Furthermore, optimal contracts cannot be replicated by short-term contracts. A family of fixed interval review contracts is characterized. Longer review intervals are preferable but harder to implement. Comparative statics on the review length are carried out. Finally, these contracts are shown approximate first best if players are very patient. (JEL D82, D86)